HANSEN’S DISEASE DIAGNOSED AFTER ANTI-CANCER CHEMOTHERAPY : (case report) - Hashmi, S. A.; Bhadauria, G. S.; Rajmohan, K. S.; Khan, I. D.; Gupta, A.; Mitra, D.; Gupta, R. M.; Rahman, M.; Kapoor, U.; Singh, S. K.; Ahmad, F. M. H. (International Journal of Medicine and Medical Research, 2020)
Background. Leprosy or Hansen’s disease is a chronic granulomatous disease involving predominantly skin, peripheral nerves and nasal mucosa but capable of affecting any tissue or organ. Histoid leprosy is a very rare well-defined clinicopathological variant of multibacillary lepromatous leprosy, which is very difficult to diagnose due to different specific clinical and histopathological ﬁndings that mimic a ﬁbromatous disorder. Histoid leprosy occurs generally after treatment failure and sometimes de novo. Objective. The aim of the study was to explore histoid leprosy throughout a case report. Methods. A case report of histoid leprosy diagnosed after cancer chemotherapy is presented. Results. A 25-year-old healthy male presented with multiple skin coloured, discrete, well defined, painless papules and nodules scattered over nape of neck, right side of the trunk and both arms along with numbness as well as tingling sensation over both the arms and trunk. It was a case of non-seminomatous germ cell tumour (NSGCT), left testis, diagnosed and treated with a high inguinal orchidectomy with adjuvant chemotherapy in 2016. Ziehl Neelsen (ZN) stain for Acid Fast Bacilli (Mycobacterium leprae) – a modified Fite stain method showed numerous acid-fast bacilli. Histopathological diagnosis of Hansen’s disease (Histoid) was conducted. The patient was admitted and started on triple drug multi-bacillary multi-drug therapy (MB-MDT). A remarkable improvement was noticed in the lesion status within one month of institution of the therapy. Conclusions. Histoid leprosy is a discrete infrequent form of multibacillary leprosy with distinctive clinical, bacteriological and histomorphological features. Histopathologic examination with modified Fite stain is still the mainstay of diagnosis.